Histopathological changes of trachea in three genetic lines of broilers vaccinated with avian infectious bronchitis virus - Latif I. kadhim; Muayad A. Hussein; Mohammed S. Abdul-Aziz (Kufa Journal for Veterinary Medical Sciences, 2016)
The histopathology of trachea was studied in three genetic lines of broilers which vaccinated with avian infectious bronchitis virus (IBV) vaccines. Differences in genetic immune response and susceptibility are known for many of the major viral pathogens of poultry. Consequently, the study was done. A total of 150 one-day-old consist of three chicken strains of broilers (Cobb 500, Ross 308 and Hubbard F-15) were assigned into six equal groups of 25 bird as fallow G1, G2 and G3 were vaccinated with IBV Ma5 and 4/91 strains at day 8 and 21 respectively, while the last three groups G4, G5 and G6 did not vaccinated with IB vaccine and remained as control groups. The result revealed that the Hubbard chicken strain had moderate to severe post vaccinal reaction represented by deciliation and necrosis of mucosal epithelia, also desquamation of goblet cells and epithelia with mild infiltration of lymphocyte in the lamina properia with blood vessels congestion after 2 days of vaccination. Then focal sloughing of epithelial mucosa with sever hyperplasia of sub mucosal glands together with mild to moderate lymphocytic infiltration blood vessels congestion and multifocal deciliation of tracheal epithelia after 10 days of vaccination. In conclusion, Hubbard chicken strain may have the lowest and slowest immune response in comparison with Ross and Cobb chicken strains.